BQ323636.1, a Novel Splice Variant to NCOR2, as a Predictor for Tamoxifen-Resistant Breast Cancer - Gong Chun; Man Ellen PS; Tsoi Ho; Lee Terence KW; Lee, Paul; Sai-Ting, Ma; Lai-San, Wong; Mai-Yee, Luk; Rakha, Emad A; Green, Andrew R; Ellis, Ian O; Lam, Eric W-F; et al. (Clinical cancer research, 2018)
Purpose: Adjuvant tamoxifen treatment revolutionized the management of estrogen receptor (ER)–positive breast cancers to prevent cancer recurrence; however, drug resistance compromises its clinical efficacy. The mechanisms underlying tamoxifen resistance are not fully understood, and no robust biomarker is available to reliably predict those who will be resistant. Here, we study BQ323636.1, a novel splice variant of the NCOR2 gene, and evaluate its efficacy in predicting tamoxifen resistance in patients with breast cancer.Experimental Design: A monoclonal anti-BQ323636.1 antibody that specifically recognizes the unique epitope of this splice variant was generated for in vitro mechanistic studies and for in vivo analysis by immunohistochemistry on tissue microarrays of two independent cohorts of 358 patients with more than 10 years clinical follow-up data, who had ER-positive primary breast cancer and received adjuvant tamoxifen treatment. An orthotopic mouse model was also used.Results: Overexpression of BQ323636.1 conferred resistance to tamoxifen in both in vitro and in an orthotopic mouse model. Mechanistically, coimmunoprecipitation showed BQ323636.1 could bind to NCOR2 and inhibit the formation of corepressor complex for the suppression of ER signaling. Nuclear BQ3232636.1 overexpression in patients samples was significantly associated with tamoxifen resistance (P = 1.79 × 10−6, sensitivity 52.9%, specificity 72.0%). In tamoxifen-treated patients, nuclear BQ323636.1 overexpression was significantly correlated with cancer metastasis and disease relapse. Nuclear BQ323636.1 was also significantly associated with poorer overall survival (P = 1.13 × 10−4) and disease-specific survival (P = 4.02 × 10−5).Conclusions: These findings demonstrate that BQ323636.1 can be a reliable biomarker to predict tamoxifen resistance in patients with ER-positive breast cancer. Clin Cancer Res; 24(15); 3681–91. ©2018 AACR.See related commentary by Jordan, p. 3480